Linalool exhibit antimicrobial ability against Elizabethkingia miricola by disrupting cellular and metabolic functions - Mingwang He; Weiming Zhong; Rongsi Dai; Su Long; Ying Zhou; Tongping Zhang; Boyang Zhou; Tao Tang; Linlin Yang; Sifan Jiang; Wenbin Xiao; YanJiao Fu; et al. (Current Research in Microbial Sciences)
Elizabethkingia miricola is a gram-negative bacillus, a life-threatening pathogen in humans and animals. Linalool, a naturally occurring monoterpene alcohol found in plant volatile oils, exhibits highly effective antibacterial properties. This study investigated the antibacterial activity and mechanism of linalool against E. miricola. Initially, linalool showed potent antibacterial activity against E. miricola, with inhibition zone (ZOI), MIC, and MBC values of 36.41 ± 1.23 mm, 0.125 % (v/v, 1.0775 mg/mL), and 0.125 % (v/v, 1.0775 mg/mL), respectively. Secondly, it was observed by electron microscopy that linalool caused crumpling, depression, and size reduction of the cells. Linalool affected cell membrane integrity, causing membrane damage and rupture. Thirdly, transcriptome analysis suggested that linalool affected C5-branched-chain dicarboxylic acid metabolism and the biosynthesis of valine, leucine, and isoleucine, result in increased energy production to linalool stress. Linalool disrupted cell division and RNA function in E. miricola, and the cells responded to linalool-induced oxidative damage by up-regulating the expression of msrB and katG genes. Fourthly, metabolome analysis revealed an increase in metabolites related to the glycerophospholipid metabolic pathway and NADP content in E. miricola, which may be a metabolic response to linalool stress. Taken together, these findings provide a theoretical basis for the antibacterial mechanism of linalool and suggest potential applications for preventing E. miricola infections.